Measurement Tool For The Adoption Of ChatGPT In Educational Institutions In Kazakhstan - Zhakupova, Aisulu; Indrawati, Indrawati; Widiyanesti, Sri (ADPEBI, 2024)
As artificial intelligence (AI) continues to revolutionize education, understanding the adoption dynamics of ChatGPT becomes increasingly vital. This study delves into the multifaceted factors influencing ChatGPT adoption within Kazakhstan’s educational realm. Key variables include electronic word-of-mouth (eWOM), peer influence, time-saving features, self-esteem, academic self-efficacy, and perceived stress. Despite concerns about academic integrity and AI-enabled cheating, there is a lack of clear guidelines governing ChatGPT’s integration into academic practices. This research sheds light on the motivations driving academics and researchers to embrace ChatGPT, emphasizing how ethical considerations shape adoption behaviors. Notably, academic self-efficacy has the most substantial positive impact on ChatGPT usage, while peer influence plays a minor role. The study collected data from 30 respondents, employing advanced methodologies for analysis. Insights reveal that ethical awareness significantly moderates the relationship between key variables, emphasizing its pivotal role in shaping ChatGPT utilization. The robust model predicts adoption behaviors effectively, offering valuable guidance for policymakers and educators in Kazakhstan.